Noxious emission reduction from liquid fuel burner via air staging method - Ishak, Mohamad Shaiful Ashrul; Mohd. Jaafar, Mohammad Nazri (Faculty of Mechanical Engineering, 2007)
Combustion implicates harmful effect to the environmental due to the emissions produced. The release of gaseous emissions such as oxides of nitrogen (NOX) and carbon monoxide (CO) into the atmosphere create major environment problems.These gaseous emissions affect plants, human being and animals. High concentration of emissions brings fatal effects to life form. Air staging or twostage combustion, is generally described as the introduction of additional/secondary air into the boiler or furnace. Staging the air into the burner(internal air staging) is generally one of the design features of low NOX burner. Staged combustion is the technique in which a high temperature, fuel rich primary zone is generated with a sufficient residence time to minimize the total fixed nitrogen that is formed in the primary zone. The secondary air mixes downstream of the primary zone to complete the combustion. Staged combustion is an effective method of controlling thermal NOX. A study has been conducted to demonstrate the effectiveness of air staging in reducing emissions from combustion process. A liquid fuel burner system with 280 mm inside diameter combustor of 1000 mm length has been investigated. All tests were conducted using commercial diesel as fuel. The study shows that a much lower NOX emissions were obtained for the staged combustion when compared to the non-staged combustion. Significant reduction of more than 15 percent of NOX emissions reduction was obtained.